DETERMINAN PENGUNGKAPAN VARIASI PERTUMBUHAN LABA ANTAR SEGMEN - Putri, Natalia Christine; Lasdi, Lodovicus (Jurnal Akuntansi Kontemporer, 2020)
The results of previous studies regarding the determinants of strategic revelation of differences in segmen earnings growth are still not consistent. This study aims to examine and analyze the factors that are determinants of strategic revelation of differences in segmen earnings growth. These factors are proprietary costs, agency costs, and financing incentives. Tests of 136 year samples using multiple linear regression show that proprietary cost tend to increase the strategic revelation of differences in segmen earnings growth. Agency cost is proven to have no effect on the strategic revelation of differences in segmen earnings growth. And financing incentives are proven to have a negative effect on the strategic revelation of differences in segmen earnings growth. The results of this study have the implication that firstly, management does not realize the losses caused by competitors. Thereby increasing the level of strategic revelation of differences in segmen earnings growth. Secondly, there is no agency conflict that can affect the level of strategic revelation of differences in segmen earnings growth. And thirdly, management dares to take risks by providing high financial incentives to obtain financing funds but do not reduce information on variations in profit growth between segments.